Development Planning with Cultural Integrity: Self-Determination, Multifunctionality, and the Hybrid Economy in Indian Country. (June 2016) - Hibbard, Michael
The experience of American Indian communities is an interesting lens through which to explore the ongoing conversation regarding the purpose and processes of development planning. This article draws on the development literature to identify and explore factors particularly relevant to the development issues faced by Indian communities. It then examines two cases in the U.S. West, the Tlingit community of Kake in Southeast Alaska and the Confederated Tribes of the Umatilla Reservation in Northeast Oregon. Finally, it draws on the results of the cases to offer some reflections on development theory and practice.